Abnormal serotonin reuptake in an overtrained, insomnic and depressed team athlete - Uusitalo, A. L. T.; Valkonen-Korhonen, M.; Helenius, P.; Vanninen, E.; Bergström, K. A.; Kuikka, J. T. (International Journal of Sports Medicine, 2004)
The purpose of this report is to study serotonin reuptake of the brain in a severely overtrained athlete by using single-photon emission computed tomography (SPECT). A 26-year-old team athlete increased his training volume (by 200 %) and intensity markedly in a new high-level team. After two months, he started to feel continuous fatigue. He had tinnitus in his left ear, he felt disturbing palpitation and had pollacisuria. After four months, he started to suffer from insomnia. He still continued to play for another three months, after which he was unable to play. He could only sleep for 3 to 4 hours per night. Only minor abnormalities could be found in extensive physical and laboratory examinations. The athlete had a severe overtraining state. In the brain SPECT scans, using the specific radioligand for serotonin transporter imaging ( (123)I labelled 2beta-carbomethoxy-3beta-[4-iodophenyl]-nortropane), low activity areas were detected in the midbrain, anterior gingulus, and left frontal and temporo-occipital lobes. In a psychiatric examination, the patient was found to have signs of major depression, which he hardly recognized himself. We conclude, that that the severe overtraining state could have been related to decreased serotonin reuptake in the brain and signs of major depression.